Studi Komparatif Kinerja Karyawan Menggunakan Fuzzy Inference System Metode Mamdani - Harmayani, H; Saleh, Khairul; Syaputra, Dwi (STIKOM Tunas Bangsa Pematangsiantar, 2021)
The problems that can be seen in the company are related to performance including there are still employees who have poor performance, seen from some employees who often violate regulations. In addition, there are still employee performance qualities that are not in accordance with the company's expectations, the persistence and hard work of employees at work are still low and have not shown satisfying results for the company. Many employees who are not disciplined in work, such as working hours are often used for resting. From the research results show to improve performance among employees at PT. Permata Hijau Palm Oleo (PHPO) Belawan is made based on criteria For each employee value data consisting of discrete (crisp) values, the simulation value will then be made. The simulation value is a value that represents each quality achievement standard with a value range of 0 – 100. In this case, a range of values for the simulation can be made as follows : Nilai 0 dan 1 memiliki rentang nilai 0 – 50, nilai 2 memiliki rentang nilai 51 – 75, Nilai 3 memiliki rentang nilai 76 – 100